Government Digital Transformation and the utilization of Basic Public Health Services by China’s migrant population - Haowen Jia (BMC Public Health)
Abstract Background This research delves into the ramifications of Government Digital Transformation (GDT) on Basic Public Health Services (BPHS) utilization among China’s migrant populace. Within the framework of escalating digital incorporation into public services, it becomes imperative to assess how GDT initiatives could ameliorate healthcare access for migrants, a group habitually confronted with systemic obstacles. Such scrutiny is crucial for the formulation of evidence-based policies that harness digital innovations to mitigate healthcare disparities. Methods The analysis employs data from the 2018 China Migrants Dynamic Survey, matched with details on the National Pilot Cities for Information Benefit to the Public policy at the prefecture city level, yielding a dataset comprising 113,905 observations. To gauge BPHS utilization among migrants, two indicators were developed: the establishment of health records and registration with family doctors. The influence of GDT on BPHS access was estimated utilizing Ordinary Least Squares regression for the initial analysis, incorporating a comprehensive array of individual and household attributes, alongside province fixed effects, to ensure a thorough evaluation. Results Baseline regression analyses revealed that GDT is significantly correlated with an enhanced probability of migrants establishing health records and registering with family doctors, with increases of 7.53% and 2.75%, respectively. Subsequent robustness checks, including sensitivity analyses with alternate dependent variables, the Propensity Score Matching method, Double/Debiased Machine Learning method, and placebo tests, further substantiated these findings. Additionally, the analysis explored mechanisms through which GDT facilitates BPHS access, identifying health information accessibility as a significant mediator in promoting healthcare engagement among migrants. Notably, both individual and regional heterogeneity were observed in GDT’s impact: female migrants, those with lower educational levels, older individuals, and rural hukou holders experienced more pronounced benefits, while the effects of GDT were also stronger in cities with lower GDP and smaller populations. These findings suggest that GDT is particularly effective in bridging healthcare access gaps in economically or demographically constrained areas. Conclusions The outcomes underscore that GDT significantly enhances BPHS utilization among migrants, positioning digital governance as an instrumental mechanism in bridging healthcare access gaps. The observed differential impacts across various subgroups and regions emphasize the importance of customized digital health strategies that cater to the diverse needs of migrant communities. For instance, targeted interventions in lower-GDP or smaller cities could maximize the benefits of GDT in under-resourced areas. Contributing to the body of empirical evidence on digital governance and public health, this research advocates for the expanded deployment of GDT initiatives to foster more equitable health service provision for migrant demographics, promoting inclusivity within a rapidly urbanizing society.